Development of SYBR green I-based real-time qPCR differential diagnosis assays for porcine reproductive and respiratory syndrome virus typing in Guangdong province - Ren, Zhaowen; Kang, Pu; Zhang, Pian; Sun, Chenglong; Chen, Jing; Xiang, Hua; Luo, Shengjun; Cai, Rujian; Huang, Yuan; Jin, Yuzhu; Wang, Gang; Wang, Xiaohu (Frontiers in Veterinary Science, 2025)
IntroductionPorcine Reproductive and Respiratory Syndrome (PRRS) is a highly contagious disease that causes reproductive disorders in sows and respiratory problems in pigs of different ages. It first appeared in the late 20th century in the United States and Europe before spreading globally, leading to significant economic losses in the swine industry. Porcine Reproductive and Respiratory Syndrome virus (PRRSV) has a high rate of genetic recombination, resulting in considerable genetic diversity within the virus. The lack of cross-protection between different lineages often leads to unsuccessful vaccination attempts.MethodsTo accurately distinguish PRRSV lineages and develop effective vaccination strategies for pigs, we have developed a fluorescence quantitative PCR (qPCR) method by designing specific primers and SYBR green dye. This method allows for the simultaneous identification of different PRRSV genotypes.ResultsOur experimental results show that these methods have good specificity and do not react with other common viral pathogens in pigs. This method also demonstrates good sensitivity, with the ability to detect low levels of the virus. The detection limits of these assay were 102 copies/μL for PRRSV-1 (European-type PRRS) and 101 copies/μL for PRRSV-2 (American-type PRRSV), HP-PRRSV (Highly Pathogenic PRRSV), and NL-PRRSV (NADC30-like PRRSV), respectively. Furthermore, the reproducibility of this method is commendable, with intra- and inter-assay coefficients of variation remaining below 3%. In the subsequent study, a total of 316 clinical samples of porcine with respiratory and reproductive failure symptoms were collected from 14 cities in Guangdong. The results showed that among these samples, 22.78% (72 out of 316) tested positive for PRRSV-2, 15.51% (49 out of 316) tested positive for HP-PRRSV, and 0.95% (3 out of 316) tested positive for NL-PRRSV. However, PRRSV-1 was not detected in any of the samples.DiscussionOur method provides a quick way to identify PRRSV genotypes in pig herds in Guangdong, which has certain significance for developing effective vaccination strategies against PRRS.